PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK SCARLETT WHITENING BODY CARE PADA MAHASISWA FEB UNIVERSITAS NEGERI MAKASSAR DI KOTA MAKASSAR - Arvina Nabila Ardhana; Anwar Anwar; Isma Azis Riu; Siti Hasbiah; Ilma Wulansari Hasdiansa (Bajang Institute, 2026)
The beauty industry in Indonesia has experienced rapid growth; however, it also faces challenges related to declining repeat purchases in certain body care product categories. This study aims to analyze the effect of brand image and price on repeat purchase decisions of Scarlett Whitening Body Care products among students of the Faculty of Economics and Business, Universitas Negeri Makassar, in Makassar City. This research employs a quantitative approach using explanatory research. Data were collected through an online questionnaire distributed to 90 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that brand image and price each have a positive and significant effect on repeat purchase decisions. Furthermore, the simultaneous test shows that brand image and price jointly have a significant effect on repeat purchase decisions of Scarlett Whitening Body Care products. These findings suggest that a strong brand image combined with a price perceived as appropriate plays an important role in encouraging consumer loyalty and repeat purchases, particularly among university students. The results of this study are expected to provide practical insights for companies in formulating marketing strategies focused on customer retention.